Navigating Academic Horizons: The Role of Location-Based Games in Multidisciplinary University Transition - Ariya, Pakinee; Intawong, Kannikar; Worragin, Perasuk; Thongthip, Phimphakan; Puritat, Kitti (International Journal of Engineering Pedagogy (iJEP), 2024)
The study focuses on the development and evaluation of a location-based game called CMU Journey, which is aimed at helping first-year students become acquainted with their new university setting during the phase of transition. The study’s three primary goals are to: (1) create a location-based game to improve knowledge acquisition related to university transition for freshmen; (2) evaluate the performance of the developed location-based game in supporting knowledge acquisition relevant to university transition; and (3) explore students’ experiences and perspectives with the location-based game designed for university transition. Using a mixed-methods approach, the study collects quantitative data through pre-post measures as well as qualitative data synthesis using an online open-ended questionnaire. Participants in the study are from Chiang Mai University’s Humanities and Social Sciences (N = 434), Technology and Science (N = 341), and Medical and Health (N = 256) programs. The findings show that students who finished the program learned considerable information about starting university, had a favorable attitude regarding studying due to the location-based game, and experienced motivation. An examination of both quantitative data from surveys and qualitative feedback from utilized data found a mix of both positive and negative comments from users. The results presented indicate the potential of location-based games as a beneficial tool for assisting with university transition, along with opportunities for future game design and implementation improvements.